Resilience to seasonal heat wave episodes in a Mediterranean pine forest. Issue 2 (21st December 2015) - Tatarinov, Fedor; Rotenberg, Eyal; Maseyk, Kadmiel; Ogée, Jérôme; Klein, Tamir; Yakir, Dan
Summary: Short‐term, intense heat waves (hamsins) are common in the eastern Mediterranean region and provide an opportunity to study the resilience of forests to such events that are predicted to increase in frequency and intensity. The response of a 50‐yr‐old Aleppo pine ( Pinus halepensis ) forest to hamsin events lasting 1–7 d was studied using 10 yr of eddy covariance and sap flow measurements. The highest frequency of heat waves was c . four per month, coinciding with the peak productivity period (March–April). During these events, net ecosystem carbon exchange (NEE) and canopy conductance ( g c ) decreased by c . 60%, but evapotranspiration (ET) showed little change. Fast recovery was also observed with fluxes reaching pre‐stress values within a day following the event. NEE and g c showed a strong response to vapor pressure deficit that weakened as soil moisture decreased, while sap flow was primarily responding to changes in soil moisture. On an annual scale, heat waves reduced NEE and gross primary productivity by c . 15% and 4%, respectively. Forest resilience to short‐term extreme events such as heat waves is probably a key to its survival and must be accounted for to better predict the increasing impact on productivity and survival of such events in future climates.